Compare the Efficacy and Safety of Modified Combined Short and Long Axis Method versus Oblique Axis Method for Right Internal Jugular Vein Catheterization in Adult Patients (The MCSLOA Trial): Study Protocol of a Randomized Controlled Trial - Tang, Jia-Xi; Wang, Ling; Nian, Wei-Qi; Tang, Wan-Yan; Tang, Xi-Xi; Xiao, Jing-Yu; Liu, Hong-Liang (Frontiers in Surgery, 2022)
Background Ultrasound-guided internal jugular vein (IJV) catheterization has become a standard procedure as it yields a higher success rate and fewer mechanical complications compared with an anatomical landmark technique. There are several common methods for ultrasound guidance IJV catheterization, such as short-axis out-of-plane, long-axis in-plane and oblique axis in-plane, but these technologies are still developing. It is important to further study the application of different ultrasound-guided IJV puncture techniques and find an effective and safe ultrasound-guided puncture technique. Methods A China randomized, open-label, parallel, single center, positive-controlled, non-inferiority clinical trial will evaluate 190 adult patients undergoing elective surgery and need right jugular vein catheterization. Study participants randomized in a 1:1 ratio into control and experimental groups. The control group will take the oblique axis in-plane method for IJV catheterization. The experimental group will take the Modified combined short and long axis method. The primary endpoint of the trial is the rate of one-time successful guidewire insertion without posterior wall puncture (PWP). Secondary endpoints are the number of needle insertion attempts, the total success rate, the procedure time, and mechanical complications. Conclusion This randomized controlled trial will evaluate the effectiveness and safety of Modified combined short and long axis method and oblique axis in-plane method for right IJV catheterization in adult patients.